INDIA GAS EXCHANGE TODAY’S REALITY AND PATH AHEAD - Patel, C.S. Divyesh; Patel, Dr. Naresh K. (Copernican Journal of Finance & Accounting, 2021)
This research aims to study structure, functioning and operational mechanism of India’s first gas exchange i.e. Indian Gas Exchange (IGX) which is a subsidiary of Indian Energy Exchange (IEX). Exploratory research is used to study and investigate conceptual framework and operational mechanism of IGX. The results of the study show that IEX has unveiled the nation’s first automated natural gas exchange trading platform called IGX for well organized and hefty Gas market and to stimulate gas trading in the country. IGX would lead India towards Gas Based Economy by designing and providing robust solution for natural gas trading and access. So far as price mechanism at IGX is concerned, it is dynamic and market driven which is based on Double-sided closed auction with uniform price mechanism. IGX plays an extremely important and fundamental role towards capitalizing a free market for gas. Clearing and Settlement system at IGX is structured and transparent. As IGX is purely electronic trading platform for natural gas which is considered as barometer of the India’s progressive policy as it integrates the entire energy value chain from gas production.